2013
DOI: 10.3109/10799893.2013.864677
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glutathioneS-transferase variants in human airway wall after long-term response to sulfur mustard

Abstract: According to these findings, we speculated that overexpression of GSTs mRNA in patients revealed that GSTs plays an important role in cellular protection against oxidative stress of MS in airway wall of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A previous study revealed that activation of autophagy in HCC could contribute to the tolerance of oxaliplatin via regulation of the level of reactive oxygen species (ROS) ( 28 ). It has been demonstrated that GSTs serve an important function in cellular protection against oxidative stress in the respiratory tract via inhibition of the endogenous production of ROS, which is increased by exposure to sulfur mustard ( 36 ). Thus, it is speculated that regulation of ROS levels may involve GSTM1 and autophagic activity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that activation of autophagy in HCC could contribute to the tolerance of oxaliplatin via regulation of the level of reactive oxygen species (ROS) ( 28 ). It has been demonstrated that GSTs serve an important function in cellular protection against oxidative stress in the respiratory tract via inhibition of the endogenous production of ROS, which is increased by exposure to sulfur mustard ( 36 ). Thus, it is speculated that regulation of ROS levels may involve GSTM1 and autophagic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have indicated that SM also reduces the glutathione peroxidase (GPX) activity in lung tissue either at chronic or acute phases. , It is a selenocysteine-containing enzyme that converts lipid and hydrogen peroxides to their corresponding alcohols and catalyzes the reducing of H 2 O 2 to H 2 O by utilizing GSH . Decreased activity of glutathione-s-transferase (GST) and glutathione reductase (GSR) enzymes has been also reported after SM exposure. ,, In a more recent study, Tahmasbpour et al have revealed higher expression of SOD , CAT , GST , GSS , and GPX mRNAs in lung biopsies of patients several years after SM exposure. However, they did not consider the expression of these antioxidants at the protein levels.…”
Section: Decreased Activity Of Antioxidant Enzymesmentioning
confidence: 99%
“…A large number of studies have considered the effect of SM on expression and activity of various antioxidant enzymes at chronic phase of injury . Although some studies have shown overexpression of different enzymatic antioxidants at the mRNA level, the activity of these enzymes or their expression at the protein level has been reported to be decreased long years after exposure to SM …”
Section: Decreased Activity Of Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of antioxidants and ROS-producing genes was significantly altered in lung tissue of SM-exposed patients (Tahmasbpour et al, 2016). Overexpression of the glutathione S-transferase (GST) variants GSTA1, GSTM1 and GSTP1 was shown in the human airway wall as a long-term response to SM (Nourani et al, 2014). …”
Section: Introductionmentioning
confidence: 99%